2017
DOI: 10.1007/s00411-017-0710-9
|View full text |Cite
|
Sign up to set email alerts
|

Boron neutron capture therapy (BNCT) translational studies in the hamster cheek pouch model of oral cancer at the new “B2” configuration of the RA-6 nuclear reactor

Abstract: Boron neutron capture therapy (BNCT) is based on selective accumulation of B-10 carriers in tumor followed by neutron irradiation. We demonstrated, in 2001, the therapeutic effect of BNCT mediated by BPA (boronophenylalanine) in the hamster cheek pouch model of oral cancer, at the RA-6 nuclear reactor. Between 2007 and 2011, the RA-6 was upgraded, leading to an improvement in the performance of the BNCT beam (B2 configuration). Our aim was to evaluate BPA-BNCT radiotoxicity and tumor control in the hamster che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Studies in canine patients with spontaneous tumors that are unresponsive or not amenable to standard treatment pave the way from translational research to clinical trials. Within this context, we performed exploratory BNCT studies in dog patients with head and neck tumors with no other therapeutic option, building on our translational BNCT studies in the hamster cheek pouch oral cancer model [ 5 , 6 , 7 , 8 , 9 , 10 ] and preparing for a BNCT clinical trial for head and neck cancer in the near future at the RA-6 clinical facility in Argentina. Complementary interest lay in contributing towards establishing an evidence-based role for BNCT in veterinary medicine based on the present study and previous BNCT studies by our group in cat patients with head and neck cancer [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in canine patients with spontaneous tumors that are unresponsive or not amenable to standard treatment pave the way from translational research to clinical trials. Within this context, we performed exploratory BNCT studies in dog patients with head and neck tumors with no other therapeutic option, building on our translational BNCT studies in the hamster cheek pouch oral cancer model [ 5 , 6 , 7 , 8 , 9 , 10 ] and preparing for a BNCT clinical trial for head and neck cancer in the near future at the RA-6 clinical facility in Argentina. Complementary interest lay in contributing towards establishing an evidence-based role for BNCT in veterinary medicine based on the present study and previous BNCT studies by our group in cat patients with head and neck cancer [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck malignancies are often radio-/chemo-resistant and undergo extensive growth, requiring mutilating surgeries [ 4 ]. Translational studies by our group in the hamster cheek pouch oral cancer model [ 5 , 6 , 7 , 8 , 9 , 10 ], exploring what was then a new target for BNCT, and clinical studies worldwide [ 11 , 12 , 13 ] have shown the therapeutic efficacy of BNCT for head and neck cancer while preserving oro-facial structures and functions. BNCT studies by our group in appropriate animal tumor models seek to contribute to the knowledge of BNCT radiobiology, optimize the therapeutic efficacy of BNCT for existing and novel targets for BNCT, and design safe and effective BNCT protocols.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that DMBA-induced squamous cell carcinomas in hamsters have similar morphological, histological and genetic features to human oral squamous cell carcinomas (8). Most of the recent research studies refer to our work as an example of an animal model of oral cancer (8,13,(14)(15)(16)(17)(18)(19)(20). Some studies have used hamster models for applying therapeutic methods such as boron neutron capture therapy (14-16), photoangiolytic treatment (17), photodynamic therapy (18), or chemopreventive compounds, including resveratrol (21), medicinal herbs (22), and phenolic compounds (23) such as apigenin and carnosic acid (19) and olive oil (20).…”
Section: Articles Citing the Foundation Report On The Hamster Model Omentioning
confidence: 93%